The effects of education on nurses' ability to recognize elder abuse induced by family members - Fatemeh Ghaffari; Atefeh Alipour; Zahra Fotokian (Kashan University of Medical Sciences, 2020)
Background: Nurses' lack of knowledge about domestic elder abuse and their limited ability to recognize it can result in negative consequences. Education has the potential to improve nurses' ability to recognize elder abuse. Yet, there is no conclusive result about its effectiveness. Objectives: The main objective of the present study was to assess the effects of education on nurses' ability to recognize elder abuse. Methods: This randomized controlled trial was conducted in two public hospitals in Ramsar and Tonekabon, Iran. Participants were 120 nurses who were randomly recruited and allocated to an intervention (n = 60) and a control (n = 60) group. The study intervention was an educational program implemented in two successive 2-h sessions in 1 day. Data were collected using a demographic questionnaire and The Nurses' Recognition of Elder Abuse by Family Caregiver Questionnaire. The possible total score of the latter questionnaire was 67-335. The data were analyzed using the Chi-square, the Fisher's exact, and the paired- and the independent-samples t-tests as well as the one-way and the repeated-measures analyses of variance. Results: The mean score of elder abuse recognition ability significantly increased in the intervention group (P < 0.001), while it did not significantly change in the control group (P = 0.85). Participants had a good ability to recognize physical elder abuse and limited ability to recognize sexual abuse. Conclusion: In-service education about elder abuse for nurses not only improves their elder abuse recognition ability but also can help them take appropriate measures for its management.